El Excentrico, 1959-03-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 5, 1959 [5 de marzo de 1959]. Ano 9, No. 13. Cover contains a photo of young musician, Gerardo Zea in mariachi attire, holding a guitar. At the time of this issue's release, he planned to study in San Jose. The headline reads, "Gerardo Zea from Montery N. Leon Boy's Town to study in S.J."